Integrasi Nilai-Nilai Keislaman dalam Pembelajaran Bahasa Indonesia untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Madrasah Ibtidaiyah - Anisa Siregar (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2026)
This research aims to analyze the effectiveness of the integration of Islamic values in Indonesian language learning on the reading comprehension skills of Madrasah Ibtidaiyah students. The method used was quantitative with a quasi-experimental design, involving class IV MI students as research subjects. The experimental class received Islamic values-based learning, while the control class received conventional learning. Data was collected through reading comprehension tests and analyzed using descriptive statistics and t-test. The research results show that the integration of Islamic values significantly increases students' reading skills, motivation, involvement, and internalization of moral values such as honesty and responsibility. This strategy supports literacy and character education holistically.